Ramp-rate control approach based on dynamic smoothing parameter to mitigate solar PV output fluctuations - Sukumar, Shivashankar; Mokhlis, Hazlie; Mekhilef, Saad; Karimi, Mazaher; Raza, Safdar (Elsevier, 2018)
In this paper a new ramp-rate control strategy based on exponential smoothing (ES) method is proposed. Different from conventional ES, the proposed method varies the smoothing parameter ‘σ’ according to PV ramp-rate. The proposed smoothing parameter is used to determine the switching status of the battery energy storage (BES). It is also used in determining the amount of power to be injected or absorbed by the BES in order to smooth the PV output power. The proposed ramp-rate control strategy is compared with moving average (MA) and conventional exponential smoothing (CES) methods. It has been found that MA and CES method exhibit memory effect that caused BES to operate all the time. The proposed ramp-rate control strategy overcomes this limitation by operating the BES only during significant fluctuation. As a result, the size of the BES capacity can be reduced and increasing its life span.